Excitation energy transfer and charge separation dynamics in photosystem II: hole-burning study - Acharya, Khem (Kansas State University, 2012)
The constituents of oxygen-evolving photosystem II core complexes—antenna proteins (CP43 and CP47) and reaction center (RC)—have been the subject of many studies over the years. However, the various issues related to electronic structure, including the origin/composition of the lowest-energy traps, origin of various emission bands, excitation energy transfer (EET), primary charge separation (CS) processes and pigment site energies remain yet to be fully resolved. Exploiting our state-of-the-art techniques such as low-T absorption, fluorescence, and hole burning (HB) spectroscopies, we resolved some of the issues particularly related to CP47 and isolated RC protein complexes. For example, we demonstrated that the fluorescence origin band maximum (~695 nm) originates from the lowest-energy state ~693 nm of intact CP47. In intact CP47 in contrast to destablished protein complexes, the band (~695 nm) does not shift in the temperature range of 5–77 K unless hole-burning takes place. We also studied a large number of isolated RC preparations from spinach, and wild-type Chlamydomonas reinhardtii (at different levels of intactness), as well as its mutant (D2-L209H), in which the active branch pheophytin (PheoD1) has been genetically replaced with chlorophyll a (Chl a). We showed that the Qx-/Qy-region site-energies of PheoD1 and PheoD2 are ~545/680 nm and ~541.5/670 nm, respectively, in good agreement with our previous assignment [Jankowiak et al. J. Phys. Chem. B 2002, 106, 8803]. Finally, we demonstrated that the primary electron donor in isolated algal RCs from C. reinhardtii (referred to as RC684) is PD1 and/or PD2 of the special Chl pair (analogous to PL and PM, the special BChl pair of the bacterial RC) and not ChlD1. However, the latter can also be the primary electron donor (minor pathway) in RC684 depending on the realization of the energetic disorder. We further demonstrate that transient HB spectra in RC684 are very similar to P+QA - PQA spectra measured in PSII core, providing the first evidence that RC684 represent intact isolated RC that also possesses the secondary electron acceptor, QA. In summary, a new insight into possible charge separation pathways in isolated PSII RCs has been provided.
Keywords: Photosystem II; Reactiion center; Hole-burning spectroscopy; Photosynthesis; Biophysics (0786); Chemistry (0485); Physical Chemistry (0494)